Քաղաքական երկխոսության հիմնախնդիրը ժողովըրդավարության անցման համատեքստում - Գալստյան, Խաչիկ (YSU Journal of International Affairs, 2016)
In this article, the author considers the problem of political dialogue through the prism of democratic transitions. In the context of the "third wave" of democratization analyzes the countries that have moved to the democratic form of government through a "big political dialogue", "round tables" and discussions. In the case of post-Soviet transformation, considering the experience of democratic transition in Armenia, the author emphasizes, that democracy in Armenia is in aconsolidation stage of its development. And in this process becomes important active introduction of dialogue forms of political communication and the creation of a culture of political dialogue.
Keywords: political dialogue, democratic transition, dialogical transition, pact agreement, culture of dialogue